2020
DOI: 10.1111/rsp3.12364
|View full text |Cite
|
Sign up to set email alerts
|

Local resistance to rising unemployment in the context of the COVID‐19 mitigation policies across Great Britain

Abstract: Policies to arrest the rapid spread of the Covid-19 pandemic resulted in whole sectors of the economy and social life being either entirely locked down or severely curtailed in the Spring of 2020. This paper uses a resilience framework to analyse two aspects of ability to resist rising unemployment at local level across Great Britain during the early part of the Covid-19 pandemic when full 'lockdown' measures were in place: (i) level of pre-lockdown unemployment; and (ii) share of employment in sectors most af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
0
20
0
1
Order By: Relevance
“…The estimated coefficient for the unemployment rate in 2015 is negative and insignificant, as shown in Column (4) of Table 3. A previous study (Houston, 2020) suggests that the unemployment level before the pandemic affects the number of unemployed during the COVID-19 pandemic. We find a similar result that low economic conditions have permanency.…”
Section: Part-time Jobsmentioning
confidence: 94%
See 2 more Smart Citations
“…The estimated coefficient for the unemployment rate in 2015 is negative and insignificant, as shown in Column (4) of Table 3. A previous study (Houston, 2020) suggests that the unemployment level before the pandemic affects the number of unemployed during the COVID-19 pandemic. We find a similar result that low economic conditions have permanency.…”
Section: Part-time Jobsmentioning
confidence: 94%
“…Unempl r is the unemployment ratio in the areas where the public employment security office, r, is located in the latest data, 2015. Houston (2020) found that the unemployment ratio before the pandemic affected the unemployment numbers after the pandemic in Great Britain. This study examines whether the local labor market conditions before the pandemic affect the number of job postings after the pandemic.…”
Section: Jp Mrt Avejp Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why identifying where this inequality escalation of social tension might start is of paramount importance. Houston (2020) presents evidence on the relationship between past levels of unemployment across regions and the experienced unemployment dynamics during the COVID-19 shock. He demonstrates that the labour market resilience of a place is dependent on its conditions from pre-pandemic times.…”
Section: Contemporary Geographies Of Deprivation In the Ukmentioning
confidence: 99%
“…Information can be linked to the COVID-19 study from the USoc which allows us to compile a study sample enriched with pre-crisis information. This is important as crisis impacts are conditioned by pre-crisis factors (Cowling et al, 2015;Houston, 2020).…”
Section: C) Gender Entrepreneurship and Psychological Factorsmentioning
confidence: 99%